ANALISIS TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KEFARMASIAN DI APOTEK UPTD PUSKESMAS BOTOMBAWO KABUPATEN NIAS TAHUN 2023 - Lubis, Rizki Ramadani; Tarigan, Palas; Mendrofa, Melza Shekinah Gloria (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2023)
Health is one of the factors that support the quality of human life. In order to create a productive society, it is necessary to improve the quality of human life. One way to improve the quality of human life is to improve the quality of health services. Patient satisfaction is a feeling of pleasure that arises in a person after getting services received or experienced directly or in other words the level of feeling of a customer after comparing the perceived performance or results. The purpose of this study was to determine the level of patient satisfaction with pharmaceutical services at the Pharmacies of the Health Center UPTD Puskesmas Botombawo, Nias Regency using a descriptive method. The sampling technique was purposive sampling. This research was conductedfrom march to April 2023. The number of samples was 83 people.. Where the results of the level of satisfaction on the responsiveness dimension are 48.1% with the category of being dissatisfied, on the reliability dimension that is 60.7% with the category of quite satisfied, on the dimension of assurance that is 59.4% with the category of quite satisfied, on the dimension of empathy that is 62.7 % with the category quite satisfied and on the dimensions of physical evidence that is 59.8% with the category quite satisfied. So that the average percentage level of patient satisfaction with pharmaceutical services at the Phermacies of the Health Center UPTD Botombawo,Nias Regency as a whole is 58.1% with the satisfaction category being quite satisfied.